2007
DOI: 10.1016/j.ijid.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Association of hemochromatosis with infectious diseases: expanding spectrum

Abstract: Withholding iron from potential pathogens is a host defense strategy. There is evidence that iron overload per se compromises the ability of phagocytes to kill microorganisms. Several hypotheses exist to explain the association of hemochromatosis with infection. A combination of mechanisms likely contributes to the increase in susceptibility to infection in these patients. A review of the current literature delineating various pathogens to which patients with hemochromatosis are potentially susceptible, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(155 citation statements)
references
References 69 publications
5
146
0
4
Order By: Relevance
“…21,22 With regard to HCT, Pullarkat et al 16 reported that ferritin levels of X1000 ng/ mL were associated with a 2-fold higher risk of bloodstream infection compared with patients with ferritin levels of o1000 ng/mL in myeloablative HCT. In agreement with their finding, in this study, ferritin levels of 4700 ng/mL were associated with a 4-fold increased risk compared with the risk in patients with levels of p700 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 With regard to HCT, Pullarkat et al 16 reported that ferritin levels of X1000 ng/ mL were associated with a 2-fold higher risk of bloodstream infection compared with patients with ferritin levels of o1000 ng/mL in myeloablative HCT. In agreement with their finding, in this study, ferritin levels of 4700 ng/mL were associated with a 4-fold increased risk compared with the risk in patients with levels of p700 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The median LOS was 7 days (5-12), which was not significantly different between the groups that received (7 days [4][5][6][7][8][9][10][11]) and did not receive intravenous iron (7 days [5][6][7][8][9][10][11][12]; P=0.29). There were 3220 patients (14.1% of the cohort) who were readmitted for infection or died from any cause within 30 days of discharge.…”
Section: Associations Of Intravenous Iron With Adverse Outcomesmentioning
confidence: 99%
“…Intravenous iron is an important part of the optimal treatment of anemia of ESRD (1), but it is biologically plausible that iron may increase infection risk by impairing neutrophil (2,3) and T cell function (4) and serving as a growth factor for pathogens (4,5). Although an association between iron and viral and fungal infections has been described (5,6), the literature in hemodialysis patients has pertained largely to bacterial infections, with a particular emphasis on systemic infections (e.g., bacteremia) (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The level of iron overload in thalassemia patients makes them more vulnerable to TB infection. 5 With current, better quality therapy, thalassemia patients can live longer, hence, the probability of exposure to TB infection is increased. 6 However, only 5-10% of people who are infected by Mycobacterium tuberculosis (MTB) will develop active TB disease.…”
mentioning
confidence: 99%